ALTERNATIVES TO IMPRISONMENT IN COSTA RICA AND THE REFORM OF ARTICLE 56 BIS OF THE CRIMINAL CODE - Ugarte Reyes, Wagner (2019)
A theoretical approach to Alternatives to imprisonment, its precedents, characteristics and execution, especially the Public Utility Service, is made from the reform of article 56 bis of the Criminal Code of Costa Rica, in force since March 2018. Sources and legal and doctrinal investigations are analyzed. It specifies the importance of supporting the transition to a criminological model that, in the face of medium and low level crimes, guarantees the rehabilitation of the offender from his community and without using the prison.